The Marketing and Brand Strategy of Shopee Indonesia in Covid-19 Era - Syiam, Nazilatus; Urfina, Yasyifa Dian; Andaru, Rizka Kurnia (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
The use of technology has driven business growth mainly due to the impressive array of information that can be presented remotely. E-commerce is one of the advances in information technology, where a system serves buyers online through computer network media. Technology presents e-commerce as an alternative transactional platform that is accepted by the public as Indonesia is the largest region with the fastest-growing e-commerce in Southeast Asia. The number of e-commerce businesses in Indonesia encourages companies to have attractive marketing strategies in order for consumers to visit e-commerce platforms and ultimately influence consumers to make purchasing decisions. In the middle of the situation with the outbreak of the Covid-19 pandemic, people are required to carry out their activities at home and maintain social distancing by recommendations of the Indonesian government. In supporting the government, Shopee declared itself to be a leading fighter on e-commerce for shopping from home with its campaign program called #ShopeeDariRumah (#ShopeeFromHome). The purpose of this paper is to find out the marketing and brand strategy of online purchase decisions at Shopee during the Covid-19 pandemic era. The results of this study prove that the website, search engine marketing, web banners, social media campaigns, and online purchase decisions have a positive and significant impact on Shopee's marketing and brand image.